The promise and perils of private voluntary regulation: Labor standards and work organization in two Mexican garment factories - Locke, Richard M.; Romis, Monica (Review of international political economy : RIPE, 2010)
What role can corporate codes of conduct play in monitoring compliance with international labor standards and improving working conditions in global supply chains? How does this system of private voluntary regulation relate to other strategies and regulatory approaches aimed at promoting just working conditions in global supply chains? This paper explores the potential and limitations of private voluntary regulation through a detailed matched pair case study of two factories supplying Nike, the world's largest athletic footwear and apparel company. These two factories have many similarities - both are in Mexico, both are in the apparel industry, both produce more or less the same products for Nike (and other brands) and both are subject to the same code of conduct. On the surface, both factories appear to have similar employment (i.e. recruitment, training, remuneration) practices and they receive comparable scores when audited by Nike's compliance staff. However, underlying (and somewhat obscured by) these apparent similarities, significant differences in actual labor conditions exist between these two factories. What drives these differences in working conditions? What does this imply for traditional systems of monitoring and codes of conduct? Field research conducted at these two factories reveals that beyond the code of conduct and various monitoring efforts aimed at enforcing it, workplace conditions and labor standards are shaped by very different patterns of work organization and human resource management policies. The promotion of these alternative work/human resources management practices can complement traditional monitoring efforts in ways that promoted improved labor standards.